Hubungan Koordinasi Mata Kaki dengan Ketepatan Shoting Ke Gawang SSB Silampari Kota Lubuklinggau - Logika Mora; Rais Firlando; Erick Salman (SJS: Silampari Journal Sport, 2021)
This study aims to determine the relationship between eye-foot coordination and the accuracy of shooting at the SSB Silampari goal, Lubuklinggau City. This type of research is quantitative research, using correlational methods. The population of this study were all 14 students of SSB Silampari with different age classifications. Sampling of the study was carried out by saturated sampling with a total sample of 14 SSB Silampari athletes. Data collection is done by eye-foot coordination test technique and shoting ability test. The collected data was then analyzed using the product-moment test. The results of the research and processing of test data can be concluded that there is a strong relationship between eye-foot coordination and the accuracy of shooting at the SSB Silampari goal, Lubuklinggau City. This is based on the value of rxy = 0.931 obtained. If the interpretation of the rxy value lies in the range of 0.80 - 1.00 which has a very strong correlation. Meanwhile, if viewed from the t-test formula, it is known that the value of tcount = 8.835 is greater than ttable = 2.17 at the 5% level.